2022
DOI: 10.1093/braincomms/fcad005
|View full text |Cite|
|
Sign up to set email alerts
|

Rehabilitation enhances epothilone-induced locomotor recovery after spinal cord injury

Abstract: Microtubule stabilisation through epothilones is a promising preclinical therapy for functional recovery following spinal cord injury that stimulates axon regeneration, reduces growth-inhibitory molecule deposition, and promotes functional improvements. Rehabilitation therapy is the only clinically validated approach to promote functional improvements following spinal cord injury. However, whether microtubule stabilization can augment the beneficial effects of rehabilitation therapy or act in concert with it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…While both drugs were effectively distributed through the blood–brain barrier, epothilone B exerted a higher effect in reducing fibrotic scarring and the number of cells and axons within the lesion and increasing serotonergic fiber regeneration and VGLUT1 distal to the lesion irrespective of rehabilitation. Thus, they concluded that epothilone B and rehabilitation acted complementarily, leading to an enhanced gait recovery [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…While both drugs were effectively distributed through the blood–brain barrier, epothilone B exerted a higher effect in reducing fibrotic scarring and the number of cells and axons within the lesion and increasing serotonergic fiber regeneration and VGLUT1 distal to the lesion irrespective of rehabilitation. Thus, they concluded that epothilone B and rehabilitation acted complementarily, leading to an enhanced gait recovery [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it significantly improved serotonergic regeneration and increased vesicular glutamate transporter 1 (VGLUT1) excitatory input into central pattern generator, thereby improving functional recovery. In combination with rehabilitation, all of these parameters were further enhanced [120].…”
Section: Use Of Pharmacological Agentsmentioning
confidence: 99%
“…Consequently, several therapeutic approaches for SCI focus on the maintenance and generation of activity in the spinal cord. Several studies highlight the link between exercise induced activity which is capable of improving axonal regeneration [179], associated with an increase in the expression of pre-synaptic markers [184,185], and specifically, pre-synaptic excitatory markers such as VGLUT1 [120,186]; and vesicular glutamate transporter 2 (VGLUT2) [110,187]. While the exact mechanism behind exercise induce locomotor function…”
Section: New Trends -Importance Of Maintaining Activity After Scimentioning
confidence: 99%
See 2 more Smart Citations